Fan beam optical tomography - Tajjudin, Mazidah (2005)
The project describes the development of a fan beam optical tomography which applied infra red sources as the sensing element. The number of sensors used in the project is very limited and that gave a significant impact on the results obtained. However, the approach of the project is concentrated on the investigation of the performance and limitations of applying infra red sensors in process tomography. Numerous optical sources had been utilized based on the fact that it is the simplest method available up till now. The advantage of infra red sources compared to other optical sources was also discussed. The importance of identifying the sensor characteristics is crucial to make sure that it is the optimum instrument for our system. This report laid some important criteria that need to be considered upon applying infrared tomography system. The developed system used four pairs of infra red sensors to interrogate a pipe having a diameter of 50 mm. The image reconstruction algorithm was built based on the Linear Back Projection Algorithm. Several experiments had been carried out to evaluate the results. The results obtained were analyzed individually and concluded at the end of the report. Some suggestions were drawn which can be considered in order to improve the system performance